2013
DOI: 10.1111/febs.12100
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of glycerol uptake in Dunaliella tertiolecta under hyperosmotic stress

Abstract: The unicellular halotolerant green alga species Dunaliella are able to proliferate in extremely varied salinities by synthesizing intracellular glycerol and adjusting the cell shape and volume. However, some marine Dunaliella species such as Dunaliella tertiolecta are not able to regulate cell volume as an immediate response to counter external osmotic shock. Here we report that a rapid shock‐response mechanism is present in Dunaliella tertiolecta, involving uptake of exogenous glycerol in response to hyperosm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Intracellular glycerol content has been found to increase with increasing content of NaCl in media [1][2][3]. It has been confirmed that yeast and other microorganisms also balance external osmotic pressure by synthesizing glycerol under hyperosmotic stress [4][5][6][7].…”
Section: Introductionmentioning
confidence: 84%
“…Intracellular glycerol content has been found to increase with increasing content of NaCl in media [1][2][3]. It has been confirmed that yeast and other microorganisms also balance external osmotic pressure by synthesizing glycerol under hyperosmotic stress [4][5][6][7].…”
Section: Introductionmentioning
confidence: 84%
“…However, a recent study by Lin et al (2013) has reported on a homolog of the GUP1 (glycerol uptake) gene in Dunaliella tertiolecta which in yeast (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomyces cerevisiae) encodes the multi-membrane protein responsible for the proton symport of glycerol (Holst et al, 2000, Lucas et al, 1990, Bleve et al, 2005, Lin et al, 2013. The D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations